Dividend Payout and Bonds Risk in Listed Companies from Malaysia - Sophee Sulong, Bin Balia; Owais, Khan; Muhammad Abdullah, Bin Zaidel (Human Resource Management Academic Research Society, 2019)
The study aims to examine the effect of dividend payout on distance to default of bonds issued by non-financial firms listed on Bursa Malaysia. For this purpose, the data is collected of 298 nonfinancial firms over the period 2006-2015. This paper focus on whether Dividend payout (hereafter abbreviate as DPO) is effect on distance to default (hereafter abbreviate as DtD). This study followed the Bharath and Shumway (2008) DtD mixtures model and combining both accounting and marketbased evidence to unravel the Malaysian corporate bonds DtD quality. The results indicated that an increase in dividend payout would results an increase in distance to default (DtD). Further indication on the determinants of DtD is found to be strong to various sensitivity examinations with different trials of variable. Bonds are increasingly playing a more critical role in the private debt intermediation process and are becoming more interconnected with financial system and more significant role in the development of corporate bonds.